The assessment of met and unmet care needs in the oldest old with and without depression using the Camberwell Assessment of Need for the Elderly (CANE): results of the AgeMooDe study - Stein, Janine; Weyerer, Siegfried (Journal of affective disorders, 2016)
Background: Depression belongs to the most common mental disorders in late life and will lead to a significant increase of treatment and health care needs in the future. The Camberwell Assessment of Need for the Elderly (CANE) evaluates met and unmet care needs in older individuals. Reports on needs of the elderly with depression are currently lacking. The aim of the present study was to identify met and unmet needs in older primary care patients with and without depression using the German-language version of the CANE. Furthermore, the association between unmet needs and depression ought to be explored. Methods: As part of the study “Late-life depression in primary care: needs, health care utilization and costs (AgeMooDe)”, a sample of 1179 primary care patients aged 75 years and older was assessed. Descriptive and inferential statistics as well as logistic regression analyses were conducted. Results: This study, for the first time in Germany, provides data on the distribution of met and unmet needs in depressive and non-depressive older primary care patients. As a main result, unmet needs were significantly associated with depression; other risk factors identified were gender, institutionalization, care by relatives and impaired functional status. Limitations: The conclusions about directions and causality of associations between the variables are limited due to the cross-sectional design. Conclusions: The study results provide an important contribution to generate a solid base for an effective and good-quality health and social care as well as to an appropriate allocation of health care resources in the elderly population.